2017
DOI: 10.1074/jbc.m116.770370
|View full text |Cite
|
Sign up to set email alerts
|

A distal ligand mutes the interaction of hydrogen sulfide with human neuroglobin

Abstract: Edited by Norma AllewellHydrogen sulfide is a critical signaling molecule, but high concentrations cause cellular toxicity. A four-enzyme pathway in the mitochondrion detoxifies H 2 S by converting it to thiosulfate and sulfate. Recent studies have shown that globins like hemoglobin and myoglobin can also oxidize H 2 S to thiosulfate and hydropolysulfides. Neuroglobin, a globin enriched in the brain, was reported to bind H 2 S tightly and was postulated to play a role in modulating neuronal sensitivity to H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…Although scavengers have many inherent problems (specificity, selectivity, delivery issues, and, unless they are catalytic, the fact they are consumed in the reactions and typically require large concentrations/ doses), in theory, this approach may also be of some merit for further exploration. However, the current state-of-the-art of H 2 S scavengers is in an embryonic stage; although heme-containing proteins (e.g., hemoglobin, myoglobin, neuroglobin) are known to scavenge H 2 S (Brunyanszki et al, 2015;Bostelaar et al, 2016;Ruetz et al, 2017;Vitvitsky et al, 2017), they also scavenge many other reactive species including nitric oxide.…”
Section: Alternative Means To Decrease Biologic H 2 S Levelsmentioning
confidence: 99%
“…Although scavengers have many inherent problems (specificity, selectivity, delivery issues, and, unless they are catalytic, the fact they are consumed in the reactions and typically require large concentrations/ doses), in theory, this approach may also be of some merit for further exploration. However, the current state-of-the-art of H 2 S scavengers is in an embryonic stage; although heme-containing proteins (e.g., hemoglobin, myoglobin, neuroglobin) are known to scavenge H 2 S (Brunyanszki et al, 2015;Bostelaar et al, 2016;Ruetz et al, 2017;Vitvitsky et al, 2017), they also scavenge many other reactive species including nitric oxide.…”
Section: Alternative Means To Decrease Biologic H 2 S Levelsmentioning
confidence: 99%
“…A). Previously reported EPR spectroscopic data demonstrates that human Ngb shows high‐spin ferric signals as well as low‐spin ones because of dissociation of distal histidine from the iron atom in the presence of disulfide bond between Cys46 and Cys55 . Unlike human Ngb, the EPR spectrum of WT Kgb did not show any sign of high‐spin signals, implying that the two axial ligands in Kgb are tightly bound to the iron atom.…”
Section: Discussionmentioning
confidence: 87%
“…However, while gaseous ligands are bound at the distal position through a heme sliding mechanism in Ngb and a distal histidine flipping mechanism in Cgb , it is unlikely that Kgb is responsible for binding gaseous ligands. Although dissociation of distal histidine from iron in Ngb is supported by the formation of a disulfide bond between Cys46 and Cys55 , such pair forming disulfide bond is absent in Kgb. Therefore, if Kgb reacts with oxygen species, it will likely undergo an outer‐sphere mechanism in which a heme–O 2 complex is not formed , while human Ngb reacts by forming a heme–O 2 complex to scavenge superoxide .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively or additionally, increased H 2 S could stimulate its oxidation by heme proteins. We have shown that globins like hemoglobin, myoglobin and neuroglobin catalyze oxidation of H 2 S to thiosulfate (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%